CHRONIC DIARRHEA IN SOLDIERS; FACTS - Hafeez, Muhammad; Saeed, Farrukh; Qureshi, Zafar; Khan, Saad Ali; Siddiqi, Fuad Ahmad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the underlying causes of chronic diarrhea in soldiers and how it differs from general population. Study Design: Prospective comparative study. Place and Duration of Study: Combined Military Hospital (CMH) Multan and Pak Emeritus Military Hospital (PEMH) Rawalpindi, from Dec 2017 to Jan 2020. Methodology: All soldiers in active service, having diarrhea more than 4 weeks in study and non-soldiers of the same age were included in the control group. There were inquired in details about the diarrhea symptoms and investigations carried out accordingly to find out the underlying cause. The two groups were compared to find out any differences. The data were analyzed by SPSS version 22. Results: Seventy one in study and 50 patients in control had their mean ages of 34.61 ± 8.35 and 32.42 ± 10.28 years. Mean duration of symptoms were 18 and 15 months in study and control groups respectively. Irritable Bowel Syndrome (IBS) was more common in both groups i.e. 14 (20%) and 20 (40%) in study and control groups respectively but frequency was more in second one. Seropositive celiac disease 13 (18.5%), seronegative villous atrophy 10 (14%) in study and Inflammatory Bowel Disease IBD 6 (12%) in control group were second most common conditions. Conclusions: Irritable bowel syndrome is common in this age group. Celiac and seronegative villous atrophy is second common conditions in the study group.